Hyperpigmentation with Vitamin B12 Deficiency in an Adolescent Girl (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Hyperpigmentation as primary symptom is rare in vitamin B12 deficiency. This adolescent non vegetarian girl presented with hyperpigmentation, anaemia, glossitis and weight loss. She was worked up to find out the cause of anemia and hyperpigmentation. Addison disease was a strong provisional diagnosis. Her cortisol level was normal and megaloblastic anemia due to vitamin B12 deficiency was found. All of her symptoms were dramatically improved by injectable cobalamin. As vitamin B12 deficiency is a treatable condition so it should be ruled out in patient presenting with hyperpigmentation. Early replacement therapy also prevents multisystem involvement like bone marrow failure and demyelinating neurological disease.J Bangladesh Coll Phys Surg 2021; 39(1): 62-67